Hubungan Kepatuhan Hemodialisis dengan Interdialytic Weight Gain (IDWG) Pada Pasien Hemodialisis - Wijayanti, Sinta; Pujiarto, Pujiarto; Dewi, Apri Rahma (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Hemodialysis is a type of kidney replacement therapy for CKD patients. The main problem that often occurs in CKD patients undergoing hemodialysis is an increase in body weight between two periods of hemodialysis or what is often called Interdialysis Weight Gain (IDWG). Increased intra-dialysis weight can cause various complications, namely intradialysis hypotension, hypertension, shortness of breath, and discomfort. One factor that can increase a patient's IDWG is hemodialysis compliance.This study aims to determine the relationship between hemodialysis compliance and IDWG of hemodialysis patients. The method used in this research is descriptive analysis with cross sectional analysis. Data collection in this study used consecutive sampling with a total research sample of 96 respondents. The research results showed that there was a significant relationship between hemodialysis compliance and IDWG of hemodialysis patients (p-value=0.013). Based on research results, it is important to know IDWG, because fluids can determine the compliance of hemodialysis patients, especially regarding problems with the patient's body fluids.  Keywords: Hemodialysis Compliance, IDWG, Hemodialysis ABSTRAK Hemodialisis merupakan jenis terapi pengganti ginjal pada pasien CKD. Masalah utama yang sering terjadi pada pasien CKD yang sedang menjalani hemodialisis adalah peningkatan berat badan diantara dua waktu hemodialisis atau yang sering disebut dengan Interdialityc Weight Gain (IDWG). Peningkatan berat badan intra dialisis dapat menyebabkan berbagai komplikasi yaitu hipotensi intradialisis, hipertensi, sesak nafas, dan ketidaknyamanan. Salah satu faktor yang dapat meningkatkan IDWG pasien adalah kepatuhan hemodialisis. Metode yang digunakan pada penelitian ini adalah analisis deskriptif dengan cross sectional. Pengambilan data pada penelitian ini menggunakan consecutive sampling dengan jumlah sampel penelitian 96 responden. Hasil penelitian diketahui terdapat hubungan yang signifikan antara kepatuhan hemodialisis dengan IDWG pasien hemodialisis (p-value=0,013). Berdasarkan hasil penelitian bahwa penting dalam mengetahui IDWG, karena peningkatan cairan dapat diketahui dari kepatuhan pasien hemodialisa khususnya pada masalah cairan tubuh pasien. Kata Kunci: Kepatuhan Hemodialisis, IDWG, Hemodialisis